[Dettifoss] - Streng, Evelyn Fiedler (1975)
Photograph of the Dettifoss waterfall. The white and brown waterfall falls from the raised portion of the land to the left, hitting water at the bottom right corner of the photograph where mist is sprayed. A flat, square mountain of white rock covered in grass sits in the background to the right. A person is sat on rocks to the right in a blue jacket.